Epigenetic regulation of brain region-specific microglia clearance activity - Ayata, Pinar; Badimon, Ana; Strasburger, Hayley J.; Duff, Mary Kaye; Montgomery, Sarah E.; Loh, Yong-Hwee E.; Ebert, Anja; Pimenova, Anna A.; Ramirez, Brianna R.; Chan, Andrew T.; Sullivan, Josefa M.; Purushothaman, Immanuel; et al. (Nature neuroscience, 2018)
The rapid elimination of dying neurons and nonfunctional synapses in the brain is carried out by microglia, the resident myeloid cells of the brain. Here we show that microglia clearance activity in the adult brain is regionally regulated and depends on the rate of neuronal attrition. Cerebellar, but not striatal or cortical, microglia exhibited high levels of basal clearance activity, which correlated with an elevated degree of cerebellar neuronal attrition. Exposing forebrain microglia to apoptotic cells activated gene-expression programs supporting clearance activity. We provide evidence that the polycomb repressive complex 2 (PRC2) epigenetically restricts the expression of genes that support clearance activity in striatal and cortical microglia. Loss of PRC2 leads to aberrant activation of a microglia clearance phenotype, which triggers changes in neuronal morphology and behavior. Our data highlight a key role of epigenetic mechanisms in preventing microglia-induced neuronal alterations that are frequently associated with neurodegenerative and psychiatric diseases. Microglia clearance activity in adult brain is regulated epigenetically and region-specifically to match neuronal attrition rates. Uncoupling this activity from neural apoptosis leads to aberrant microglia activation & neurodegenerative-like changes.